Pembelajaran Matematika Materi Pecahan di SDN Nglegok 1 Blitar dengan Menggunakan Media Game Pecahan (MAGECAH) - Haikal Cahaya; Ida Putriani; Ida Putri Rarasati (Pentagon : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
This research evaluates the effectiveness of using game-based learning media, MAGECAH, in teaching Mathematics on the topic of fractions in the 4th grade at SDN Nglegok 1 Blitar. The method used is a quasi-experiment with a nonequivalent control group design. The sample consists of 52 students, divided into experimental and control groups. Research instruments include tests, questionnaires, observations, and documentation. The analysis results show that the MAGECAH media significantly improves students' understanding, with a t-test significance value of 0.000. This media is also considered effective in making learning more interactive and engaging. Thus, MAGECAH can become an innovative alternative in Mathematics learning, particularly in the topic of fractions, to improve students' learning outcomes.